The Influence of Abiotic Factors on the Distribution of Macrophytes in Small Water Bodies in Temperate Ecosystems - Isabel Navarro Law; Isabelle Durance; Rachel Benstead; Michael E. Fryer; Colin D. Brown (Limnological Review)
Currently, reviews focusing on the distribution of macrophytes focus primarily on large water bodies, regardless of the fact that small water bodies (SWBs), such as ponds, ditches and streams, often support higher levels of gamma macrophyte richness. This review investigates the direction and strength of the relationship between 13 abiotic factors and macrophyte distribution in SWBs. Results demonstrate that there are distinct differences between the effects of abiotic factors on bryophytes and those on vascular macrophytes of different morphological forms. Whilst shading and velocity have a significant (p < 0.05) negative relationship with vascular macrophyte richness and a positive relationship with bryophyte richness, the reverse is true for the size of a water body, depth and concentration of nitrogen. Vascular macrophyte richness has a significant (p < 0.05) negative relationship with distance to a stream source, isolation, the proportion of surrounding land that is woodland, total phosphorus concentrations and pH. The strength of the influence of substrate size and water body size differs between vascular macrophyte morphologies. Key knowledge gaps include bryophyte distribution and the effect of hydroperiod and surrounding land use on macrophyte communities. In order to conserve all macrophyte morphologies and taxa, it is important to protect SWBs with a diverse set of conditions.